(untitled) (Sound Stage Screen, 2024)
This paper offers an acoustemological exploration of a set of taped interviews on the subject of witchcraft made in the 1960s and 1970s by historian and ethnomusicologist Cesare Bermani in the village of Villa Zaccheo (Abruzzo, Italy). Bermani’s extraordinary research has resulted in a celebrated monograph as well as more than 90 hours of taped interviews and songs made available through the Archivio Cesare Bermani in Orta San Giulio (Novara, Italy). Beginning with a few examples from Bermani’s taped interviews (which we transcribe and thickly describe so as to render their overall aural effect), we investigate the role of feeling and listening in the interviewees’ perception of witches. In particular, we observe the way interviewees recount the role of hearing in their encounters with witches (and the particular declination of “acousmatic” listening that results from it), as well as the interviewees’ complex relationship to the recording apparatus and microphone. We then excavate the importance of the legal and conceptual category of “hearsay” in the long political history of European witchcraft, and point out some of the long-standing political implications of this category for recent oral histories. Finally, we offer some preliminary conclusions on the ways in which voice, listening, recording technology and language (Italian as well as dialect), as well as shifting constructions of gender, combine to render the figure of the witch in oral history, in the hope of laying the groundwork for future re-evaluations of the relationship of sound, media, and the construction of the witch.